DESCRIPTION OF PATIENTS WITH ODONTECTOMY IN RSUD SULTAN FATAH DEMAK - Fuad Fatkhurrohman; Syarifah Nova Amiza Zam; Dea Hardyana Putri; Khairunnisa Pulungan; Isnadia Rachmah Ika (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: Odontectomy is the surgical removal of teeth. The choice of anesthesia is also one of the considerations in the odontectomy surgical technique. Information regarding gender, age and comorbidities in patients can also be considered in the selection of anesthetics for odontectomy procedures. Purpose: to provide information regarding impacted teeth and to determine the frequency distribution of odontectomy patient profiles at the Oral Surgery Polyclinic of Sultan Fatah General Hospital, Demak Regency. Methods: descriptive study by collecting secondary data using a retrospective approach from medical records from visits to the Oral Surgery Polyclinic, Sultan Fatah Demak Regional General Hospital from 8-12 May 2023. Results and Discussions:  a total of 36 patients were obtained on 8-12 May 2023, with 32 patients who met the inclusion criteria. The majority of patients were male with a percentage of 55.6%. Based on the age of the most patients in the age range of 21-30 years (15 patients), while the least age group is the age group <20 years (4 patients). Based on the type of teeth, the most odontectomy performed was tooth 48 with a total of 14 teeth. Conclusion: The distribution of the frequency of odontectomy patients at Sultan Fatah General Hospital is most commonly found in the male sex, age group 21-30 years, the type of tooth that was odontectomy was tooth 48.